GAMBARAN TINGKAT PENGETAHUAN REMAJA TENTANG BAHAYA NARKOBA DI SMP KRISTEN IMMANUEL - Lyana Arsianti; Nor Aisah; Ike Gunawarsiah (Jurnal Nurse, 2020)
Drugs or drug is a material / substance / dangerous drug, drug effects when consumed in small doses several lead someone into hallucinations that made sleep and unconsciousness. Knowledge Immanuel Christian teenagers in junior class VII is indispensable in knowing the dangers of drugs. By increasing students' knowledge, the risk will be reduced dealt drugs. Purpose: For an overview of age, gender, level of knowledge of adolescents about the dangers of drugs in immanuel Christian Junior High seventh grade. Methods: The method used is a descriptive study conducted at Immanuel Christian Smp class VII. The sample used by 45 respondents. The tools used in this research is data collection questionnaire. Analysis of the data used in this study is Univeriate. Results: Based on the research results indicate that as many as 11 to 12 years Adolescents Adolescents (24.4%), 13 years as many as 12 youth (26.7%), age 19 Youth 14 Youth (42.2%), and Youth 15 total 3 Teens (6.7%). Based on the analysis the researchers showed that as many as 20 male youth (44.4%) and women as much as 25 youth (55.6%). Based on the research level respondents extensive knowledge High Youth as many as 31 (68.89%), adolescents knowledgeable that as many as 10 youth (22.22%), as well as adolescents who are knowledgeable lower by 4 teenagers (8.89%). Conclusion: From these results it can be concluded that the majority of adolescent knowledge level about the dangers of drugs at very high immanul Christian junior class VII, as many as 42 respondents (93.33%).